Photoreforming of biomass in metal salt hydrate solutions. Issue 43 (24th April 2020) - Pichler, Christian M.; Uekert, Taylor; Reisner, Erwin
Abstract : A combined process using LiBr metal salt hydrates and photoreforming converts cellulosic biomass into H2 and organic reaction products. Abstract : Metal salt hydrate (MSH) solutions allow for the complete solubilisation of biomass and we demonstrate its use as a reaction medium for the photocatalytic reforming of lignocellulose. Different types of photocatalysts such as TiO2 and carbon nitride can be employed in MSH to produce H2 and organic products under more benign conditions than the commonly required extreme pH aqueous solutions.